2022
DOI: 10.1094/pdis-04-21-0864-re
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Analysis of Fungal Species Associated with Blast and Brown Spot Diseases of Oryza sativa

Abstract: Fungal diseases; blast, and brown spot in rice incur severe yield losses worldwide. Blast is caused by Magnaporthe oryzae, while Bipolaris oryzae is reported as the main causal organism of brown spot. Both diseases cause leaf lesions which are difficult to be differentiated by symptomatology until the late stages. Early detection and differentiation of the lesions would help the adoption of disease management strategies specific to the pathogen and will prevent the native impact on the quality and quantity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Standard isolation protocol was followed to isolate B. oryzae and S. oryzae , and their identity was confirmed based on morphological and molecular techniques (Peeters et al., 2020; Terensan et al., 2022). The fungal pathogens were cultured and maintained on potato dextrose agar (PDA) medium, and the bacterial cultures were maintained on the nutrient agar (NA) medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard isolation protocol was followed to isolate B. oryzae and S. oryzae , and their identity was confirmed based on morphological and molecular techniques (Peeters et al., 2020; Terensan et al., 2022). The fungal pathogens were cultured and maintained on potato dextrose agar (PDA) medium, and the bacterial cultures were maintained on the nutrient agar (NA) medium.…”
Section: Methodsmentioning
confidence: 99%
“…Standard isolation protocol was followed to isolate B. oryzae and S. oryzae, and their identity was confirmed based on morphological and molecular techniques (Peeters et al, 2020;Terensan et al, 2022).…”
Section: Culturing Of Fungal Pathogens and Bacterial Strainsmentioning
confidence: 99%
“…Similar results were noticed by Jaiganesh and Kannan [20] who studied about the pathogen characters and pathogenicity of B. oryzae. Terensan et al [21] studied the morphological and molecular analysis of the brown spot pathogen in Sri Lanka. Singh et al [22] confirmed the morphological characterization of Bipolaris oryzae based on the growth characteristics of the isolates.…”
Section: Morphological Characterization Of B Oryzaementioning
confidence: 99%
“…It is a fungal ailment that primarily affects rice plants, targeting various plant parts such as leaves, glumes, seedlings, sheaths, stems, and grains of mature plants. The presence of dark coffee-colored spots is notable in the panicle, and severe infestations can lead to spot formation in the grains, resulting in reduced yield and compromised milling quality (Terensan et al, 2022).…”
Section: Brown Spotmentioning
confidence: 99%